2016
DOI: 10.1080/17461391.2016.1143036
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine improves muscular performance in elite Brazilian Jiu‐jitsu athletes

Abstract: Scientific information about the effects of caffeine intake on combat sport performance is scarce and controversial. The aim of this study was to investigate the effectiveness of caffeine to improve Brazilian Jiu-jitsu (BJJ)-specific muscular performance. Fourteen male and elite BJJ athletes (29.2 ± 3.3 years; 71.3 ± 9.1 kg) participated in a randomized double-blind, placebo-controlled and crossover experiment. In two different sessions, BJJ athletes ingested 3 mg kg(-1) of caffeine or a placebo. After 60 min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 41 publications
6
83
3
1
Order By: Relevance
“…Results showed that power increased with all loads with caffeine ingestion, except for the bench press velocity at 1 m•s -1 (p = 0.06, Cohen's d = 0.68). Using the same dose of caffeine in a group of 14 Brazilian jiu-jitsu athletes, Diaz-Lara et al [69] confirmed that caffeine may be ergogenic for power, showing an increase in maximal power and mean power in the bench press exercise.…”
Section: Effects Of Caffeine On Powermentioning
confidence: 94%
“…Results showed that power increased with all loads with caffeine ingestion, except for the bench press velocity at 1 m•s -1 (p = 0.06, Cohen's d = 0.68). Using the same dose of caffeine in a group of 14 Brazilian jiu-jitsu athletes, Diaz-Lara et al [69] confirmed that caffeine may be ergogenic for power, showing an increase in maximal power and mean power in the bench press exercise.…”
Section: Effects Of Caffeine On Powermentioning
confidence: 94%
“…The participants responded to an 8-item survey regarding the incidence of side effects ("yes/no" response scale). This survey was also used to examine side effects in previous research that explored effects of caffeine on exercise performance [20,22,23].…”
Section: Side Effectsmentioning
confidence: 99%
“…Surprisingly, only seven studies (43.8%) reported using normality tests. 15,16,[20][21][22][23][24] However, the normality tests were on small samples (n = 10 to 18), which produce an inherent bias because such samples tend to have nonparametric distributions. 25 Only three studies (18.8%) performed analyses of the blinding procedures.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…The type of contraction does not seem to be a key factor because five other studies using isometric contractions reported ergogenic effects. 21,22,[26][27][28] The five studies that did not observe increased strength included volunteers not habituated to caffeine or with low caffeine consumption and four of them 20,24,29,30 evaluated the strength of smaller muscle groups. Hence, the ergogenic effects of CAFF were present in voluntary muscle contraction in eleven (68.8%) of the 16 analyzed studies.…”
Section: Caffeine Effect On Strengthmentioning
confidence: 99%
See 1 more Smart Citation